Bioremediation techniques applied to aqueous media contaminated with mercury. (1st November 2016) - Velásquez-Riaño, Möritz; Benavides-Otaya, Holman D.
Abstract: In recent years, the environmental and human health impacts of mercury contamination have driven the search for alternative, eco-efficient techniques different from the traditional physicochemical methods for treating this metal. One of these alternative processes is bioremediation. A comprehensive analysis of the different variables that can affect this process is presented. It focuses on determining the effectiveness of different techniques of bioremediation, with a specific consideration of three variables: the removal percentage, time needed for bioremediation and initial concentration of mercury to be treated in an aqueous medium.